‘Here’s Me Being Humble’: The Strangeness of Modeling Intellectual Humility - Clemente, Noel L (Archīum Ateneo, 2023)
There’s something paradoxical with a person saying ‘I am humble’; it doesn’t seem so humble to self-attribute humility in general, and intellectual humility in particular. In light of the recent interest in educating for intellectual virtues, this paradox has interesting implications to educating for intellectual humility. In particular, one might wonder how a teacher can be a model of intellectual humility to her students. If a teacher says something like ‘Here’s me being an exemplar of intellectual humility’, the paradox above takes on a pedagogical angle. In this paper, I analyze the paradoxes in self-attributing and learning intellectual humility using three different accounts of this virtue, before proceeding to untangle what could be called the ‘Modeling Paradox’ of teaching intellectual humility and figure out whether this virtue can be non-problematically demonstrated to one’s students.